SPOTS STRUCTURE AND STRATIFICATION OF SOMECHEMICAL ELEMENTS IN THE ATMOSPHERE OF He-WEAK STAR HD 21699 - Shavrina, A. V.; Glagolevskij, Yu. V.; Silvester, J.; Chuntonov, G. A.; Pavlenko, Ya. V.; Khalack, V. R. (Одеські астрономічні публікації, 2008)
---